CHANGING THE SYSTEM OF LAND RELATIONS AND RURAL DISPLACE-MENT WITHIN THE PEASANT COMMUNITY IN THE IMPLEMENTATION OF STOLYPIN AGRARIAN REFORM: MODERNIZATION OR RESTORATION - Kuznetsov, Dmitry (Revista Inclusiones, 2020)
The article deals with the issues of the correspondence of land relations and rural displacement, resulting in the implementation of Stolypin agrarian reform, to the ancient forms of Russian peasantry’s community organization. Objective: To determine whether the Stolypin agrarian reform was an unfamiliar phenomenon for the traditions of community daily living activities in the Russian village. The historical genetic method will allow us to consider the evolutionary nature of changes taking place in the system of land relations within the peasant community during the implementation of Stolypin reform. Using the ideographic method, we will describe the unique and exceptional features of the Russian community, ensuring its long-term existence and functioning. The retrospective method will allow us to consistently penetrate deep into the historical past of the Russian peasant community. By means of the comparative-historical method an attempt will be made to provide the comparative and contrastive analysis of the situation existed in the Russian village during the Stolypin reform regarding the similar processes taking place in the Russian village during the Middle Ages. The historical and typological method will allow us to provide classification, by means of which it will be possible to determine the essence of the peasant community by identifying its main constituent elements. The diachronic method will be used to compare the main features of peasant community in different periods of its historical existence.